EXPERIENCE: A CONNECTION CHANNEL WITH OTHERS - Freitas, Sandra (Journal of Social Pedagogy, 2018)
In this article, we search through authors like Benjamin and Larrossa, reflect on "experience", how it touches us, transforms us and connects us with the people who experience similar experiences, identifying them as sister souls, not we become indifferent to his pain. We bring to dialogue, teaching situations and learning, especially those related to the literacy of children of the working classes, whose experiences of failures, experienced by their teachers as students, them to become attuned to these children, making them to them through a sensitive listening of their life stories, the understanding of taste bitterness that failure causes in people's lives and the realization that learning process can be facilitated through a with those who find obstacles to their learning through a persevering, competent and loving attitude of the teacher, for all to learn, none less!